Training Driver Go-Jek Indonesia Guna Meningkatkan Kualitas Pelayanan - Lyris Lyris; A.A.N. Oka Suryadinatha Gorda (Jurnal Manajemen dan Bisnis, 2016)
This study aims is to determine how training process in PT. GO-JEK Indonesia, to seehow effective is the training maintaining the quality of service, and also providing analternative of training program that appropriate. This research is descriptive research withqualitative methods. Data were obtained by interview, observation, and documentation fromGO-JEK’s driver and consumers who’s used GO-JEK.Training process of GO-JEK’s driver can be divided into two phases, it is SOPtraining and defensive riding training. Based on the results of the evaluation carried out byusing Kirkpatrick’s evaluation model, the conclusion is SOP training not effective enough tomaintain the quality of service if viewed from the perspective of the drivers. While defensiveriding training is effective enough in maintaining the quality of service if viewed from theperspective of the drivers.From the discussion, it was concluded that the SOP training has not been sufficientlyeffective, that’s why make a alternative training model is needed. The alternative trainingmodels are change the location training, number of trainees, and make the program moreinteresting, create a quis in the end of the program, making a program that reminding aboutthe rules in GO-JEK, and create a system where management conduct surveillance.Keywords: training, evaluation, Kirkpatrick